The T2K near detector data acquisition systems - Thorpe, M; Angelsen, C; Barr, G; Metelko, C; Nicholls, T; Pearce, G; West, N (2011)
T2K is a second generation long-baseline experiment in Japan, designed to perform precision studies of neutrino oscillations. A neutrino beam originating at the J-PARC facility is sampled by two near detectors, approximately 280 m distant from the source and directed towards the Kamioka underground facility, 295 km distant, where the Super-Kamiokande water Cerenkov detector is situated. Both the on-axis (INGRID) and off-axis (ND280) near detectors employ the MIDAS framework for their data acquisition systems. Events are selected via a flexible hardware trigger, which allows mixed operating modes incorporating beam spill, cosmic and calibration triggers. Data are acquired from the front-end electronics over optical Gigabit Ethernet links by custom MIDAS front-end applications distributed over a cluster of Linux computers. Event fragments from all sub-detectors are merged and logged on a central backend processor and then copied to remote storage for long-term archival. The system is also designed to allow flexible partitioning of sub-detectors for standalone diagnostics and calibration. We present the design of the DAQ system and report on experience gathered during early operation of the near detectors. © 2006 IEEE.